FPGA design and implementation for adaptive digital chaotic key generator - Elsayed, Ghada; Soleit, Elsayed; Kayed, Somaya (Bulletin of the National Research Centre, 2023)
Background Information security is very important in today’s digital world, especially cybersecurity. The most common requirement in securing data in all services: confidentiality, digital signature, authentication, and data integrity is generating random keys. These random keys should be tested for randomness. Hardware security is more recommended than software. Hardware security has more speed and less exposure to many attacks than software security. Software security is vulnerable to attacks like buffer overflow attacks, side-channel attacks, and Meltdown–Spectre attacks. Results In this paper, we propose an FPGA Implementation for the adaptive digital chaotic generator. This algorithm is proposed and tested before. We introduce its implementation as hardware. This algorithm needs a random number seed as input. We propose two designs. The first one has an input random number. The second one has PRNG inside. The target FPGA is Xilinx Spartan 6 xc6slx9-2-cpg196. We used MATLAB HDL Coder for the design. We propose a configurable Key block’s length. For 32 bit the maximum frequency is 15.711 MHz versus 11.635 MHz for the first and second designs respectively. The area utilization of the Number of Slice Registers is 1% versus 2%. The number of Slice Look Up Tables is 40% versus 59%. number of bonded input output blocks is 64% versus 66%. otherwise are the same for the two designs. Conclusions In this paper, we propose an efficient and configurable FPGA Design for adaptive digital chaotic key generator. Our design has another advantage of storing the output keys internally and reading them later.